Effects of Environmental Relative Vorticity and Seasonal Variation on Tropical Cyclones over the Western North Pacific - Yusi Wu; Shumin Chen; Mingsen Zhou; Yilun Chen; Aoqi Zhang; Chaoyong Tu; Weibiao Li (Atmosphere, 2022)
An improved understanding of the environmental factors influencing tropical cyclones (TCs) is vital to enhance the accuracy of forecasting TC intensity. More than half of TCs that were substantially affected by environmental factors were predominantly affected by low-level environmental relative vorticity (hereafter, VOR TCs). In this study, the seasonal variation and related physical features of VOR TCs from 2003–2017 during TC seasons in summer and autumn over the western North Pacific were analyzed. Autumn VOR TCs exhibited the strongest intensity among all TCs over the western North Pacific. The enhanced environmental relative vorticity during the TC intensification period was larger and more favorably distributed for VOR TC development in autumn. The vorticity diagnostic analysis showed that the convergence was the positive source of environmental relative vorticity of VOR TCs, while the contribution of convergence was larger in autumn than in summer. The increased convergence was related to seasonal variation in larger-scale systems, especially the higher environmental pressure gradient, which reflected the larger subtropical high and the compressed East Asian summer monsoon trough in autumn. In addition, the East Asian summer monsoon trough was also somewhat stronger during the intensification period of VOR TCs, especially in autumn.